2020
DOI: 10.3390/ijerph17239144
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Officially Ordered Restrictions during the First Wave of COVID-19 Pandemic on Physical Activity and Quality of Life in Patients after Kidney Transplantation in a Telemedicine Based Aftercare Program—A KTx360° Sub Study

Abstract: Guidelines recommend a healthy lifestyle and regularly physical activity (PA) after kidney transplantation (KTx). The KTx360° program is a multicenter, multisectoral, multimodal, telemedicine-based follow-up care program. Effects of the first COVID-19 wave restrictions on health-related quality of life and PA of supervised KTx360° patients were evaluated using an online questionnaire. Six hundred and fifty-two KTx360° patients were contacted via email and were asked to complete the Freiburg questionnaire of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…General well-being, PH, and PsH are linked with PA. PA is also affected by the COVID-19 lockdown, negatively impacting the HRQoL. PA played a pivotal role in improving HRQoL, especially in the comorbidities reported by Hanke et al (2020). In the context of PA related to our findings, similar results were reported in Greece and found adverse changes in PA due to the COVID-19 lockdown (Bourdas and Zacharakis, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…General well-being, PH, and PsH are linked with PA. PA is also affected by the COVID-19 lockdown, negatively impacting the HRQoL. PA played a pivotal role in improving HRQoL, especially in the comorbidities reported by Hanke et al (2020). In the context of PA related to our findings, similar results were reported in Greece and found adverse changes in PA due to the COVID-19 lockdown (Bourdas and Zacharakis, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…The sample size ranged from 164,101 ( 100 ) to 18 ( 40 ) participants. In terms of quality assessment, there were a total of 2 unsatisfactory studies ( 51 , 91 ), 36 satisfactory studies ( 21 , 23 , 25 , 26 , 28 , 33 , 36–38 , 40 , 41 , 43 , 44 , 47 , 48 , 52–57 , 59–64 , 67 , 68 , 71 , 77 , 78 , 81–83 , 92 ), 42 good-quality studies ( 22 , 24 , 27 , 29–32 , 34 , 39 , 42 , 45 , 46 , 49 , 50 , 57 , 58 , 61 , 65 , 66 , 69 , 70 , 72–74 , 76 , 79 , 80 , 84–90 , 93–98 , 100 ), and 2 very good-quality studies ( 35 , 99 ). Tables 1 – 5 show further details on the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“… 21 , 22 This may also be useful in maintaining patients’ adherence and well‐being. Hanke et al, 23 who reported on a telemedicine‐based aftercare program for kidney transplant recipients, concluded that this program was effective in maintaining physical activity and quality of life during the first wave of the COVID‐19 pandemic. The pandemic highlights the advantages of such telemedicine and eHealth tools and could facilitate their broader implementation.…”
Section: Discussionmentioning
confidence: 99%